Effect of cement dust pollution on the vascular cambium of Juglans regia (L.) - Bilal Ahmad Wani; Amina Khan (African Journal of Environmental Economics and Management, 2023)
Woody trees increase in girth by the activity of meristematic tissue called vascular cambium. The vascular cambium comprises fusiform and ray initials, which give rise to vertically oriented elements that is, vessels, fibers, tracheids etc. and horizontally oriented elements that is, rays. The present study reveals that there is reduction in dimensions and proportions of fusiform and ray initials in Juglans regia growing under impact of cement dust pollution.